Morocco : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2003)
The Financial System Stability Assessment of Morocco reviews the reform program that is aimed at establishing a modern, market-oriented financial system that optimizes the mobilization of savings and the allocation of financial resources. It reviews the modernization of the banking sector and the development of competition within the sector, development of financial markets, and removal of constraints on financial system activity. It also provides reports on the Observance of Standards and Codes on Insurance Regulation, Securities Regulation, Payment Systems, and Monetary and Financial Policy Transparency.